Au nanostar nanoparticle as a bio-imaging agent and its detection and visualization in biosystems - Perevedentseva, E. (Biomed Opt Express, 2020)
In the present work, we report the imaging of Au nanostars nanoparticles (AuNSt) and their multifunctional applications in biomedical research and theranostics applications. Their optical and spectroscopic properties are considered for the multimodal imaging purpose. The AuNSt are prepared by the seed-meditated method and characterized for use as an agent for bio-imaging. To demonstrate imaging with AuNSt, penetration and localization in different biological models such as cancer cell culture (A549 lung carcinoma cell), 3D tissue model (multicellular tumor spheroid on the base of human oral squamous carcinoma cell, SAS) and murine skin tissue are studied. AuNSt were visualized using fluorescence lifetime imaging (FLIM) at two-photon excitation with a pulse duration 140 fs, repetition rate 80 MHz and 780 nm wavelength femtosecond laser. Strong emission of AuNSt at two-photon excitation in the near infrared range and fluorescence lifetime less than 0.5 ns were observed. It allows using AuNSt as a fluorescent marker at two-photon fluorescence microscopy and lifetime imaging (FLIM). It was shown that AuNSt can be observed inside a thick sample (tissue and its model). This is the first demonstration using AuNSt as an imaging agent for FLIM at two-photon excitation in biosystems. Increased scattering of near-infrared light upon excitation of AuNSt surface plasmon oscillation was also observed and rendered using a possible contrast agent for optical coherence tomography (OCT). AuNSt detection in a biological system using FLIM is compared with OCT on the model of AuNSt penetrating into animal skin. The AuNSt application for multimodal imaging is discussed.